2004
DOI: 10.1080/11026480410033557
|View full text |Cite
|
Sign up to set email alerts
|

Health promotion as school development

Abstract: Background: Data obtained from international studies of health behaviour among school-age children show evidence of strong relationships between alienation from school and health behaviour such as smoking, alcohol use, physical activity and food choices. This article discusses these connections between health problems and underachievement. Objective: The aim is to raise the question of whether, and if so, how school development could be a way to handle both the alienation and the health problems. Design and Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
(11 reference statements)
0
10
0
Order By: Relevance
“…An analysis of the similarities between the learning process and the salutogenic model has been reported, as the learning process is facilitated when the information is structured and comprehensible and thus becomes meaningful [6]. It has been therefore suggested that integrating the salutogenic perspective in all activities and programmes in school also means that health promotion becomes integrated with school development [46]. Finally, one of our main findings was that lower levels of SOC were associated with increased suicidal risk.…”
Section: Erickson Et Al (2007) Systematic Review Found That Soc Has Anmentioning
confidence: 65%
“…An analysis of the similarities between the learning process and the salutogenic model has been reported, as the learning process is facilitated when the information is structured and comprehensible and thus becomes meaningful [6]. It has been therefore suggested that integrating the salutogenic perspective in all activities and programmes in school also means that health promotion becomes integrated with school development [46]. Finally, one of our main findings was that lower levels of SOC were associated with increased suicidal risk.…”
Section: Erickson Et Al (2007) Systematic Review Found That Soc Has Anmentioning
confidence: 65%
“…The salutogenic model here becomes a tool for the enhancement of QoL. Further, integrating the salutogenic perspective in all activities and programmes in school also means that health promotion becomes integrated with school development 77. Further, a model based on the salutogenic perspective has been developed, with the special aim of evaluating education on different levels in the European Union 78…”
Section: Resultsmentioning
confidence: 99%
“…Schools are widely recognised as one environment in which healthy lifestyles can be promoted . Due to their structured nature, schools can tackle the obesity epidemic through a combination of strategies: embedding nutrition and healthy living into curriculum, development and modelling of healthy food cultures, effective communication on healthy eating strategies and the availability of healthy food from the school canteen.…”
Section: Introductionmentioning
confidence: 99%